Professional musicians, university teachers: How can research be added, and why is it so important? - Bennett, Dawn (Curtin University, 2003)
Professional classical instrumental music is traditionally a male-dominated profession, and yet increasing numbers of women join the ranks of the world's professional orchestras, or make careers as soloists and conductors. Careers in classical music performance typically are short, lasting until the mid-thirties or forties at which time the impact of attrition factors such as sporadic employment, unsociable hours and travel are further compounded as practitioners respond to the demands of family commitment.The decrease of career mobility most affects women, who are likely to be the primary care givers for their children. A broader base of skills would enable musicians to diversify their professional roles so that they are better able to manage a career that enables them to juggle both professional practice and a range of other activities.According to current research, the reality of careers in classical music has yet to be considered by many educators, trainers and employers. These findings are consistent with the current literature, which indicates that research into the management of music careers is vital, and that education has a major role to play both in the research and the subsequent application of findings into new educational opportunities.This paper presents findings of a study within a Doctoral research program. The ability to access multiple roles is particularly important for women trying to maintain professional practice in a field where increased success corresponds to increased travel with longer periods away from home, and equally for women academics who combine professional practice with university teaching and research.The implications for university music educators include designing programs that effectively equip musicians for sustainable careers, and meeting the urgent need for research that must be accommodated within already crowded professional and personal lives.